Legal Issues of EU Accession to the European Convention on Human Rights - Ghazinyan , A. (Bulletin of Yerevan University C: Jurisprudence, 2016)
EU human rights policy has been developed by the European Court of Justice in the course of 50 years of its functioning, though initially the Treaties on EU did not contain any provision on the protection of human rights and fundamental freedoms. Following the Lisbon Treaty and adoption of EU Charter on Fundamental Rights the road to accession of EU to the European Convention on Human Rights was opened and the accession process was launched. On December 18, 2014, the ECJ adopted the opinion 2/13, regarding the compliance of Accession treaty with the Lisbon Treaty, where it indicated certain issues stating that the Accession treaty bears potential danger for the autonomy of EU laws.
Keywords: European Union, European Convention on Human Rights, European Court of Justice, Europan Court of Human Rights, Case law, EU Accession to the European Convention on Human Rights, ECJ Opinion 2/13